A Multi‐Functional Implant Induces Bone Formation in a Diabetic Model. Issue 18 (19th August 2020) - Khorsand, Behnoush; Acri, Timothy M.; Do, Anh‐Vu; Femino, John E.; Petersen, Emily; Fredericks, Douglas C.; Salem, Aliasger K.
Abstract: Patients with diabetes mellitus (DM) have defective healing of bone fractures. It was previously shown that nonviral gene delivery of plasmid DNA (pDNA) that independently encodes bone morphogenetic protein‐2 ( BMP‐2 ) and fibroblast growth factor‐2 ( FGF‐2 ), acts synergistically to promote bone regeneration in a DM animal model. Additionally, both insulin (INS) and the hormonally active form of vitamin D3, 1 α, 25‐dihydroxyvitamin D3 (1 α, 25(OH)2 D3 ) (VD3) have independently been shown to play key roles in regulating bone fracture healing in DM patients. However, these individual therapies fail to adequately stimulate bone regeneration, illustrating a need for novel treatment of bone fractures in diabetic patients. Here, the ability of local delivery of INS and VD3 along with BMP‐2 and FGF‐2 genes is investigated to promote bone formation ectopically in Type‐2 diabetic rats. A composite consisting of VD3 and INS is developed that contains poly(lactic‐ co ‐glycolic acid) microparticles (MPs) embedded in a fibrin gel surrounded by a collagen matrix that is permeated with polyethylenimine (PEI)‐( pBMP‐2 + pFGF‐2 ) nanoplexes. Using a submuscular osteoinduction model, it is demonstrated that local delivery of INS, VD3, and PEI‐( pBMP‐2 + pFGF‐2 ) significantly improves bone generation compared to other treatments, thusimplicating this approach as a method to promote bone regeneration in DM patients with bone fractures. Abstract : The local delivery of insulin, Vitamin D3 metabolites, and BMP‐2 and FGF‐2 genes from a collagen scaffold is investigated to promote bone formation in Type‐2 diabetic rats. The ectopic formation of bone in diabetic rats suggests this approach has strong potential for bone regeneration in diabetic patients.